2014
DOI: 10.1016/j.psychres.2013.11.020
|View full text |Cite
|
Sign up to set email alerts
|

The power to resist: The relationship between power, stigma, and negative symptoms in schizophrenia

Abstract: Stigmatizing beliefs about mental illness can be a daily struggle for people with schizophrenia. While investigations into the impact of internalizing stigma on negative symptoms have yielded mixed results, resistance to stigmatizing beliefs has received little attention. In this study, we examined the linkage between internalized stigma, stigma resistance, negative symptoms, and social power, or perceived ability to influence others during social interactions among people with schizophrenia. Further, we sough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 44 publications
0
19
0
1
Order By: Relevance
“…As a result, some research on self-stigma using the ISMIS calculates a self-stigma score that excludes Stigma Resistance subscale or examines this sub-scale separately (Lysaker et al, 2012;MashiachEizenberg et al, 2013;Park et al, 2013). More recent studies have examined the item loadings of the ISMIS and conclude that the Stigma Resistance items comprise a distinct factor from the remainder of the ISMIS, and recent studies have also demonstrated adequate reliability of this sub-scale in samples with schizophrenia spectrum disorders (Campellone et al, 2014;Nabors et al, 2014). Next, while the Positive Aspects subscale scores of the Stigma Scale have shown adequate reliability (King et al, 2007), it remains infrequently used.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, some research on self-stigma using the ISMIS calculates a self-stigma score that excludes Stigma Resistance subscale or examines this sub-scale separately (Lysaker et al, 2012;MashiachEizenberg et al, 2013;Park et al, 2013). More recent studies have examined the item loadings of the ISMIS and conclude that the Stigma Resistance items comprise a distinct factor from the remainder of the ISMIS, and recent studies have also demonstrated adequate reliability of this sub-scale in samples with schizophrenia spectrum disorders (Campellone et al, 2014;Nabors et al, 2014). Next, while the Positive Aspects subscale scores of the Stigma Scale have shown adequate reliability (King et al, 2007), it remains infrequently used.…”
Section: Introductionmentioning
confidence: 99%
“…Since patients included in this research were post-acute, this can explain this correlation 17,18 . There was no correlation between stigma resistance subscale and insight, which implies that this subscale is related to some other variables yet to be determined 19,20 . There were several limitations to the study important to consider.…”
Section: Vidović Et Almentioning
confidence: 80%
“…When the context is sensitive, as in this paper, there is a risk to the participants' welfare. The participants' wellbeing may be affected, and if the information on their participation would be made public, they can suffer social consequences due to the stigmatization of mental health illnesses such as schizophrenia [14]. During the interviews, the relatives of people with schizophrenia expressed concern that if their participation became known, it would negatively affect their children.…”
Section: Ethicsmentioning
confidence: 99%
“…Designing an e-health system for people diagnosed with schizophrenia means encountering contradictory and sensitive problems that affect the design situation, such as paranoia and delusions [8], and social stigmatisation [13,14]. These types of problems that are contradictory, incomplete or have constantly changing requirements, have previously been referred to as "wicked problems" [cf.…”
Section: Introductionmentioning
confidence: 99%